Apical Hypertrophic Cardiomyopathy and Myocardial Infarction in a Young Adult, a Rare Combination - Datta, Gautam; Mukherjee, Dipankar; Bhubanmajhi, DM; Singh, Rupesh; Bhattacharya, Sudhir (Journal of Medicine, 2013)
A teenage boy of 19 years without traditional risk factors for coronary artery disease, presented with typical anginal pain with ST-T changes in anterior leads and elevated cardiac troponin T. Investigation revealed the patient having apical hypertrophic cardiomyopathy with normal coronary angiography and a spade shaped apex on LV angiography. With a diagnosis of microvascular infraction, further investigations revealed elevated LP (a), serum homocysteine and low HDL probably playing a contributory role. DOI: http://dx.doi.org/10.3329/jom.v14i1.14557 J MEDICINE 2013; 14 : 74-76